MOTIVATION OF WOMEN'S ENTREPRENEURSHIP AS AGENT OF CHANGE IN SOCIETY: Literature Review - Eny Yuniati; Heri Pratikto; Sopiah Sopiah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study is a literature review which is considered important with the increasing number of female entrepreneurs who make a positive contribution to revitalizing the country's economy. Not only men who can do entrepreneurship, nowadays many women are also making an effort to revive their family's economy. In the current situation, many find it difficult to get a job where socio-economic conditions are uncertain which creates many opportunities for women to open new business opportunities independently. In running a business, motivation is needed to keep running what has been established. This study aims to dig up information through literature studies related to how women are motivated to run independent businesses in order to meet their economic and social needs presented by several researchers who are used as empirical sources in this study. This research method uses a literature review by summarizing the results of previous studies that have been carried out. Based on this study, it was found that women's entrepreneurial motivation comes from two factors, namely external factors and internal factors. While the motivation for women's entrepreneurship as agents of change is the existence of women who are entrepreneurs who have an impact on changes in the family environment and community environment.